Cross-Channel Behavior in Indonesia: Are Omnichannel Shoppers More Loyal than Multichannel Shoppers? - Annetta Gunawan; Ujang Sumarwan; Lilik Noor Yuliati; Siti Jahroh (Bina Nusantara University, 2022)
The retail industry in Indonesia is still in the transition phase from multichannel to omnichannel. Hence, the behavior of shoppers is divided into two broad categories, namely multichannel and omnichannel shoppers. The research aimed to know the socio-demographic characteristics of multichannel and omnichannel shoppers in Indonesia. It also tested the difference between both in showing cross-channel behavior and loyalty to the retailers. The data were obtained by questionnaires from 341 respondents with purposive sampling. The descriptive method with cross-tabulation analysis was applied to capture the socio-demographic characteristics of multichannel and omnichannel shoppers. Meanwhile, the comparative method with an independent sample t-test tested the difference between both types of shoppers in showing cross-channel behavior and loyalty to the retailers. The results show that millennial and female shoppers are the most potential segment at this time to be targeted in the context of omnichannel retailing. Both multichannel and omnichannel shoppers are dominated by those whose income is less than Rp4,5 million to Rp10 million with 3 to 5 persons in their household. Moreover, there are significant differences between multichannel and omnichannel shoppers in the context of cross-channel behavior and loyalty. Omnichannel shoppers show cross-channel behavior and loyalty more than multichannel shoppers.